Role of Foreign Employment in Socioeconomic Development of Beldandi Rural Municipality, Kanchanpur, Nepal - Thakuri, Bir Bahadur Singh (Scholars' Journal, 2022)
This study is about the role of foreign employment in socio-economic development of Beldandi rural municipality. The main objective of this study is to analyze the nature and the role of foreign employment in the socio-economic development of Beldandi Rural Municipality of Kanchanpur district. A micro-level case study type research design was applied in which primary data were collected from a household survey with random sampling methods. A semi-structured questionnaire was applied for primary data where secondary data related to foreign employment were collected from different published sources. Simple mathematical procedures were used to analyze the data. The study findings show that 85 percentage of households got economic security by increasing their economic status from remittance income, and 65 percentages of respondents improved their knowledge and skills and used their skills in their community after arrival. This study also shows that foreign employment has positive changes in the socioeconomic status of respondents. However about 11percent of respondents’ economic status is worse, 35 percent of respondents’ socioeconomic status did not changes and around 54 percent of the respondent’s social attitude changed due to foreign employment.